Study and research of power amplifier in neural stimulation system - Liu, Hongbo (2016)
Neural stimulation has been in use since a long time, with different techniques being used for treatment existing in the market today. However, most of them which have been successful, use implant techniques for high efficacy of treatment. This is because wireless transmission of power is a challenge. The amplifier required to produce the electric field for stimulation is of critical importance in this case. In this report, we analyze different kinds of amplifiers, study their characteristics and compare them. Implementation of a class-D power amplifier is performed, and modulation of waveform output is performed using simulation techniques for a class-D amplifier for the desired output. Key words: neural stimulation, amplifier network, class-D amplifier